A importância do setor de serviços na economia brasileira: um Estudo da PAS/IBGE - Bezerra, Jéssica Maria de Brito (Universidade Federal Rural do Semi-Árido, 2020)
The importance of the service sector's activities in our society can be demonstrated by the position it occupies in the economy, whether through participation in GDP or in job creation, and by analyzing the trends and transformations that the world economy is experiencing. Aiming at mapping the Brazilian reality on the service sector, IBGE initiated and improved the performance of the Annual Service Survey (PAS), whose objective is to identify the basic structural characteristics of the service provider activities, allowing to estimate the number of companies, personnel occupied, salaries, revenues, costs and expenses, as well as building indicators such as: average income, average salary, etc. This study aims to identify the main changes in the profile of the service sector in Brazil between the periods 2007 and 2017, according to the Annual Service Survey conducted by IBGE. In addition, its specific objectives are to identify the methodology and groups of service activities investigated by PAS and collect the main indicators provided by PAS in the years 2007 and 2017. This is a documentary survey, with secondary quantitative data, which were collected through IBGE's SIDRA system. As a result, there was a great growth in this 10-year period, where the service sector started to become more consolidated and important for the country's economy, being one of the sectors with the greatest contribution to GDP.
Keywords: Serviços; IBGE; Economia; Services; Economy; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO